Tinjauan Pustaka: Literasi Dasar pada Siswa Kelas 1 Sekolah Dasar melalui Pembelajaran Membaca Permulaan - Dea Prananda; Sahrini Amir; Nur Jelita Lauli; Sulastya Ningsih (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2026)
Basic literacy serves as the cornerstone of academic success; however, beginning reading skills among first-grade elementary school students remain notably underdeveloped. This study aims to examine how beginning reading instruction contributes to basic literacy and to identify key factors that support its success. A Systematic Literature Review (SLR) employing a qualitative descriptive approach was utilized. Data were sourced from three national journals, retrieved through Google Scholar using keywords such as basic literacy, beginning reading, and first-grade elementary students. From 20 initially identified articles, four met the inclusion criteria and were analyzed using content analysis techniques. Findings indicate that students face challenges in letter recognition, distinguishing similar-shaped letters, and combining syllables, attributed to internal factors (e.g., low motivation and cognitive limitations) and external factors (e.g., monotonous teaching methods and insufficient parental involvement). Various interventions proved effective: the Picture Word Inductive (PWI) model increased reading skills from 69% to 86%; picture card media raised early reading abilities from 30.83% to 91.6%; and the digital Mora Game demonstrated high effectiveness with an N-Gain score of 73.35%. Successful literacy depends on engaging media, child-centered approaches, collaborative support from teachers and parents, and the wise pedagogical use of technology. Early intervention is crucial to preventing persistent reading difficulties and establishing a robust academic foundation for students.